A tributação como instrumento de redução da desigualdade de renda e riqueza: uma abordagem do plano internacional ao plano local - Anselmini, Priscila (Universidade do Vale do Rio dos Sinos, 2019)
Given the growing inequality of income and wealth, especially in the Brazilian territory, the dissertation proposes to analyze taxation as an instrument to reduce the concentration of income and wealth, by adopting alternatives to the exclusionary national tax system. At this juncture, the research analyses the level of income and wealth inequality present in Brazil, as well as in the United States and France, to further examine whether or not the national tax system contributes to the development of this scenario. At this moment, the structure of the current Brazilian tax burden, especially concerning taxation on consumer and service goods, and income; and possible changes, aiming for the “common good”; and the reduction of income inequality are analyzed. From this perspective, it is clear that inequality of wealth must also be tackled, considering it is even more prominent than that of income. Consequently, there is currently a discussion about the taxation on capital, both nationally and internationally, being considered a mechanism capable of reducing the concentration of wealth, as well as to regain control of financial capitalism, as such a measure is capable of creating a more equal distribution of the global private wealth, especially in Brazil. To this end, the research used, used as bibliographical sources, such as legal books, official reports, newspapers, periodicals, magazines and precedents. For all these reasons, the dissertation is justified to analyze the real possibility of adopting changes in the current national tax model, to have an effective reduction of income and capital inequalities, allowing the maintenance of fundamental rights for all Brazilian citizens.
Keywords: Desigualdade de renda e riqueza; Tributação sobre os bens de consumo e serviços; Imposto de Renda; Tributação sobre o Capital; Income and wealth inequality; Taxation on consumer goods and services; Income tax; Taxation on capital; ACCNPQ::Ciências Sociais Aplicadas::Direito